Kearifan Lokal Petani di Kawasan Pertanian Kuok Kabupaten Kampar Provinsi Riau - Rizqi Sari Anggraini; Eliartati Eliartati; Rathi Frima Zona (xxxx-xxxx, 2020)
Anggraini RS, Eliartati E, Zona RF.  2020.  Farmer’s local wisdom in kuok agricultural land kampar regency of Riau province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Innovation and technology adoption are important to increase rice production and productivity. This study aimed to know the agricultural technology that was used by farmers, and to understand the adoption of Jarwo Super Technology that disseminated to the farmers as well. This study was conducted in Empat Balai and Pulau Jambu Villages Kuok Sub-district Kampar Regency, since January -  Agustus 2020. The results showed that there were differences between Jarwo Super and farmers’ conventional farming technique. The differences between Jarwo Super and farmer’s conventional farming were the amount of seeds per planted hole, the use of fertilizers and agricultural mechanization usage. The rice production using Jarwo Super Technology was higher than conventional method. Jarwo Super Rice technology was able to increase rice production in Empat Balai village from 4.2 T/ha to 4.75 T/ha, and in Pulau Jambu village from 4.2 T/ha to 4.55 T/ha. Some of Jarwo Super components were able to accepted by the farmers. However, there were some local wisdoms that were still be applied by the community, including the use of traditional harvesting tools.